Effectiveness of Reverse Engineering STEM-ESD on Students’ Creative Problem-Solving Ability: A Quasi-Experimental SDG-12 Topic Study - Syifa Nur Shadrina; Riandi Riandi; Ari Widodo (Integrated Science Education Journal, 2026)
Purpose of the study: This study examines the effectiveness of a Reverse Engineering-based STEM-Education for Sustainable Development (STEM-ESD) learning model in improving tenth-grade students’ Creative Problem Solving (CPS) Thinking ability on the SDG-12 topic, compared with an Engineering Design Process-based STEM-ESD (STEM-EDP) model and conventional instruction. Methodology: A mixed-methods explanatory sequential design combined a quasi-experimental non-equivalent control-group pretest–posttest design with 108 tenth-grade students in three intact classes (STEM-RE, STEM-EDP, and Control) at a public senior high school in Bandung, purposively selected at the class level, and semi-structured interviews with 9 purposively selected students. Quantitative data were analyzed using normalized gain (N-Gain), the Shapiro–Wilk normality test, the Kruskal–Wallis test, and the Mann–Whitney post hoc test with Bonferroni correction in SPSS; qualitative data were analyzed using Braun and Clarke’s thematic analysis. Main Findings: The STEM-RE group achieved the most consistent improvement in CPS Thinking across all four indicators (N-Gain = 0.255–0.301), with statistically significant differences among the three groups (Kruskal-Wallis and Mann-Whitney, p < 0.05). Idea flexibility was the only indicator to reach the moderate category, while the STEM-EDP group showed fluctuating, low-category gains and the Control group showed negligible or negative change. Novelty/Originality of this study: This study provides indicator-level comparative evidence that a Reverse Engineering-based STEM-ESD sequence, contextually integrated with SDG-12, produces more consistent CPS Thinking gains than an Engineering Design Process-based alternative within the same sustainability context a comparison not previously reported thereby advancing both creative problem-solving pedagogy and sustainability-oriented science education.